Nelarabine neurotoxicity with concurrent intrathecal chemotherapy: Case report and review of literature. (August 2015) - Ngo, Dat; Patel, Samit; Kim, Eun Jeong; Brar, Rondeep; Koontz, Michael Z
Severe nelarabine neurotoxicity in a patient who received concurrent intrathecal (IT) chemotherapy is reported. A 37-year-old Caucasian woman with a history of T-cell lymphoblastic lymphoma was admitted for relapsed disease. She was originally treated with induction chemotherapy followed by an autologous transplant. She developed relapsed disease 10 months later with leukemic involvement. She was re-induced with nelarabine 1500 mg/m 2 on days 1, 3, and 5 with 1 dose of IT cytarabine 100 mg on day 2 as central nervous system (CNS) prophylaxis. At the time of treatment, she was on continuous renal replacement therapy due to sequelae of tumor lysis syndrome (TLS). She tolerated therapy well, entered a complete remission, and recovered her renal function. She received a second cycle of nelarabine without additional IT prophylaxis one month later. A week after this second cycle, she noted numbness in her lower extremities. Predominantly sensory, though also motor and autonomic, peripheral neuropathy started in her feet, ascended proximally to the mid-thoracic region, and eventually included her distal upper extremities. A magnetic resonance imaging (MRI) of her spine demonstrated changes from C2 to C6 consistent with subacute combined degeneration. Nelarabine was felt to be the cause of her symptoms. Her neuropathy stabilized and showed slight improvement and ultimately received an unrelated, reduced-intensity allogeneic transplant while in complete remission, but relapsed disease 10 weeks later. She is currently being treated with best supportive care. To our knowledge, this is the first published case report of severe neurotoxicity caused by nelarabine in a patient who received concurrent IT chemotherapy.